2017
DOI: 10.3389/fmed.2017.00105
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Conjunctivitis due to Chlamydia felis—Case Report, Review of the Literature and Improved Molecular Diagnostics

Abstract: A 29-year-old woman presented with unilateral, chronic follicular conjunctivitis since 6 weeks. While the conjunctival swab taken from the patient’s eye was negative in a Chlamydia (C.) trachomatis-specific PCR, C. felis was identified as etiological agent using a pan-Chlamydia TaqMan-PCR followed by sequence analysis. A pet kitten of the patient was found to be the source of infection, as its conjunctival and pharyngeal swabs were also positive for C. felis. The patient was successfully treated with systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
15
0
3
Order By: Relevance
“…Since C. felis has poor environmental persistence, direct contact is needed for transmission [ 24 , 52 ]. It has been shown in the past that higher positivity rates could be associated with certain environmental risk factors such as outdoor access and living in a multi-cat environment, which increases the number of contacts between cats [ 22 , 44 , 46 ]. Halánová et al confirmed that a higher density of animals is most likely associated with higher chlamydial infection rates, and, according to Hwang et al, the prevalence of pathogens that are transmitted through direct contact is higher in areas where stray cats are being fed and therefore gather in groups [ 46 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since C. felis has poor environmental persistence, direct contact is needed for transmission [ 24 , 52 ]. It has been shown in the past that higher positivity rates could be associated with certain environmental risk factors such as outdoor access and living in a multi-cat environment, which increases the number of contacts between cats [ 22 , 44 , 46 ]. Halánová et al confirmed that a higher density of animals is most likely associated with higher chlamydial infection rates, and, according to Hwang et al, the prevalence of pathogens that are transmitted through direct contact is higher in areas where stray cats are being fed and therefore gather in groups [ 46 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has also been detected in dogs and was recently found in a free-ranging Eurasian lynx suffering from conjunctivitis [ 1 , 12 , 15 , 16 ]. Zoonotic transmissions are rarely reported, except for a few cases in which C. felis was found to be the cause of keratoconjunctivitis or follicular conjunctivitis in men [ 19 , 20 , 21 , 22 ], demonstrating its potential risk for zoonotic infections for humans with close contact to diseased animals in particular [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conjunctivitis in human has previously been found in a case report involving an HIV-positive patient whose infection was traced back to a personal pet kitten which tested positive for non- trachomatis Chlamydia [142]. A similar case was recently reported in a woman who contracted unilateral chronic conjunctivitis from her C. felis -positive kitten [143]. Cases such as these are rare, but contribute to the increased likelihood of a threat of zoonosis.…”
Section: Introductionmentioning
confidence: 90%
“…Currently, porcine are the only known natural host. The zoonotic transmission of C. suis has been described among farmers in the porcine slaughterhouse through screening, although there is no clear signs of a symptomatic infection [87,88,89,142,143]. The isolation of a tetracycline-resistant strain of C. suis has raised considerable concerns within the porcine farming industry, especially regarding the fear of horizontal transfer of the tetracycline resistant Tet (C) gene to other human chlamydial pathogens [160].…”
Section: Introductionmentioning
confidence: 99%
“…caviae and C . felis in human eyes 19 , 66 , 67 . In our study, one sequence obtained in the aTT group and one in the cTF group demonstrated highest homology to C .…”
Section: Discussionmentioning
confidence: 99%